Religious Education and Community Development: A Study on the Pondok and Its Efforts to Realize the Philosophy of Islamic Education - Abdulroya Panaemalae, Abdul Razak @ (Al-Albab, 2015)
The work is trying to show how relevant the pondok education is with the philosophy of Islamic education itself. The research recognize that there are still many weaknesses that need to be changed in the education system of the pondok, so that they continue to stand and live to provide the religious spirit to every Muslim as has been proved before. Yet these benefits outweigh the weaknesses. It should not be repealed. It is important to find new formulas to empower this institution in line with the changes in time. It is something which has been proven to be good and useful to mankind, so there is no need to bother to change it. Although there are wooden frames and a roof that need to be replaced, and water wells that should be constructed to ensure the water flows, but again there is no need to destroy what has been strongly built. The good values of each item are fixed. It is also the role of pondok education in religious education that has played an effective role in order to form a noble personality and civilized humans in accordance with the Islamic principles.